Kidney cancer website www.rak-nerki.pl (in Polish) as an accomplishment of the idea of progress - Wcisło, Gabriel (Contemporary Oncology/Współczesna Onkologia, 2008)
The idea of progress has been associated with a certain version of progressivism which stems from directional transformation, which means the change from a given state to another one. Therefore, a practical interpretation embraces leaving the state of primary cultural poverty, ignorance, and sense of being lost to higher levels of civilization. The idea of progress still plays pivotal roles in the development of modern medicine, which has triumphed for many years. To make real rules that present the heart of the idea of progress is possible only when civilizational progress has earlier come true. So it is not possible to gain innovations (in fact, they are the markers of progress) in medicine without cultural development, appearance of new technology, and social development. The internet is a worldwide network of connected computers which cooperate with each other at the level of data transfer. Physicians are a part of modern society or postmodern society, and like the rest of humans, they are changed similarly to others. Additionally, physicians bear responsibility for a high quality of work. The internet appears to be a good medium to exchange information which can be used for interpersonal communication, enter-tainment, education, business activity or industrial production purposes. Profes-sional internet portals give possibilities to make a virtual reality that is able to exist due to a virtual community. The latter consists of real humans working in various professions, for instance physicians. An individual person (e.g. a physician) is a part of the professional network. Further individual progress ensures that a given physician will be a crucial element of the network through his or her skills to get necessary data or to make professional databases broader.